Organic and Inorganic Waste Management in an Efforts to Empower Santri at the Burhanul Hidayah Islamic Boarding School, Sidoarjo - Zakkiy Fasya, Abdul Hakim; Ibad, Mursyidul; Naila El Muna, Kuuni Ulfah (UNUSA Press, 2024)
The main problem faced by Burhanul Hidayah Islamic Boarding School is that awareness of the existence and impacts of poor waste management remains low due to a lack of knowledge and understanding about waste and how to manage it. The boarding school, which has more than 380 students, has the potential to implement independent and sustainable waste management. Community service activities at Burhanul Hidayah Islamic Boarding School include training on waste management to increase students' awareness. This training covers sorting and classifying waste into organic and non- organic types. After sorting, students receive training on processing organic waste into fertilizer that can be used to enrich the soil within the boarding school environment. Non-organic waste, such as coffee wrappers, detergent packaging, and similar items, is processed into creative products that are valuable, economical, and usable in daily activities. Based on the results of the waste education and processing activities, it can be concluded that there has been an increase in students' awareness and knowledge of waste management. Students are now capable of transforming both organic and non- organic waste into products with added value.